Analisis Tingkat Kepuasan Masyarakat Terhadap Program Bank Ramli di Kota Samarinda - Febrianti Soleha; Erwiantono; Heru Susilo; Freddy Maryanto (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2023)
Empowerment program that develops the potential of villages around the company's area related to utilization, environmental management, improvement of health facilities and improvement of community skills. The purpose of this study is to improve service providers in improving the quality of service of the Ramli Bank Program. The sampling method used purposive sampling. The data analysis method used descriptive analysis, consumer satisfaction index (CSI), and importance performance analysis (IPA). The results of the analysis showed that the CSI is 84.28%, meaning that consumers are very satisfied with the performance of Bank Ramli Ceseri. IPA analysis showed that the main priority in improvement so that customer satisfaction can be increased by the accuracy of the submission schedule and the realization of the CSR assistance program. While the satisfaction index is 78.44%, meaning that consumers are satisfied with the performance at Bank Ramli Perseka. Efforts to increase the level of customer satisfaction, so it is necessary to make improvements to the existing attributes. IPA analysis showed that the top priority in improvement so that customer satisfaction can increase with the disclosure of information about service procedures.